The Development and Evaluation of the French Version of the Schwartz Outcome Scale-10 (SOS-10-F) - Laux, John M.; Young, Jennifer L.; McLaughlin, Laura; Perera-Diltz, Dilani (Canadian Journal of Counselling and Psychotherapy, 2007)
The Schwartz Outcome Scale-10 (SOS-10; Blais et al., 1999) is an effective measure of change in inpatient (Blais et al.) and outpatient populations (Hilsenroth, Ackerman, & Blagys, 2001), as well student counselling centers, chemically dependent populations, and in research projects (Laux & Ahern, 2003; Young, Waehler, Laux, McDaniel, & Hilsenroth, 2003). The utility of the SOS-10 in Canada is limited because there is currently no French version of this instrument. This study reports on a three-phase process (initial translation from English to French, evaluation of the on-line English SOS-10, and establishing equivalency between English on-line and French on-line versions) of development and validation of a French version of the SOS-10.